NIMG-09. DETECTION OF ASYMPTOMATIC MALIGNANT LESIONS BY [18F]FDG PET/MRI IN CHILDREN AND ADOLESCENTS WITH NEUROFIBROMATOSIS TYPE 1. (12th November 2021) - Baumgartner, Alicia-Christina; Platzgummer, Hannes; Aszmann, Oskar; Amann, Gabriele; Berghoff, Anna; Kasprian, Gregor; Traub-Weidinger, Tatjana; Azizi, Amedeo A
Abstract: BACKGROUND: Plexiform neurofibromas (PN) are a hallmark feature of Neurofibromatosis type 1 (NF1). 10% of PN undergo malignant transformation. As malignant peripheral nerve sheath tumors are a leading cause of death in NF1-patients, early detection of malignancy is essential. 2-deoxy-2-[ 18F]fluoro-D-glucose [ 18 F]FDG PET/CT imaging is used in patients with NF1 to judge malignant transformation. AIMS: The present study evaluated [ 18 F]FDG PET/MRI in pediatric NF1 patients at high risk for MPNST and its utility as a possible screening tool for malignant transformation of yet asymptomatic lesions. METHODS: Patients aged 0-25 with symptomatic and asymptomatic neurofibromas who underwent PET/MRI from 2014 to 2021 were included. Chart review of imaging data, clinical and histological findings was performed retrospectively. RESULTS: 41 patients (18 female) with a median age at first PET/MRI of 16.87 years (6.21-24.41) were included. 40 lesions were operated as indicated by clinical (e.g. pain, rapid growth) or imaging findings. Based on histopathological analysis 7 lesions in 4 patients were categorized as malignant, 3 as atypical neurofibromatous neoplasms of uncertain biologic potential (ANNUBP). 4/7 malignant and 2/3 ANNUBP lesions were asymptomatic (i.e. without rapid growth, pain, neurologic dysfunction). 5/7 symptomatic tumors were without significant FDG-PET and proven benign by histology. 18 lesions (2 symptomatic) in 9 patients that showed an increased uptake suspect of malignant transformation were histologically classified as benign. None of the patients died during follow-up, 1 symptomatic MPNST patient received postsurgical radio- and chemotherapy. CONCLUSION: Our data indicate that malignant transformation of PN also occurs in asymptomatic patients. [ 18 F]FDG PET/MRI is feasible in pediatric and adolescent patients with the tumor predisposition syndrome NF1 and is an alternative to PET/CT when assessing for malignancy thereby drastically reducing radiation exposure. Early detection through screening of high-risk NF1 patients with [ 18 F]FDG PET/MRI could potentially increase overall survival by facilitating early curative resection.